You can run - Zanetti, Rebecca (Zanetti, Rebecca. Laurel Snow thriller, 2022)
With a serial killer on the loose in Genesis Valley, WA, FBI profiler Laurel Snow must negotiate her conflicting feelings for the fish and wildlife officer she is working with, while dealing with a growing list of suspects and a danger that's far too close to home.